Enhancement Of Oat Milk Suspension Stability Via Enzyme Hydrolysis Manipulation - Nasrudin, Nurshatila (Pusat Pengajian Teknologi Industri, 2021)
Objective of this study was to produce nutritious and stable oat milk by applying multi-enzyme combination. Oat milk plant-based alternative is made up of suspension particles, which come from insoluble plant materials such as cellulose, hemicellulose and pectin that prone to sedimentation and result in instability of oat milk. Viscozyme L contain variety of carbohydrases was used to hydrolyzed suspension particles and reduce its particles size as well as liberated the nutrient incorporated in polysaccharide matrices.